Pharmacovigilance in Paediatric Population: An Evolving Landscape in Drug Safety Monitoring (Mugda Medical College Journal, 2025)
Adverse drug reactions (ADRs) represent one of the major health problems worldwide which have high morbidity and mortality rates. The risk of ADR is higher in paediatric patients for various reasons. But knowledge about ADR in children is very poor. Adequate recognition of ADR is challenging in paediatric population. Because of their unique physiological and developmental traits, children—from neonates to adolescents – a particularly difficult demographic for drug treatment. When compared to adults, these alterations can have a substantial impact on pharmacokinetics and pharmacodynamics, resulting in changes in drug absorption, distribution, metabolism, and excretion. Historically, paediatric groups have been overlooked in clinical medication studies, resulting in insufficient data on their safety and efficacy. To address this gap, adult research has been extrapolated to children, with changes in body size and maturation, but without an extensive understanding of developmental pharmacology. Therefore, to maximize therapeutic results and reduce harm, adverse drug reactions (ADRs) in children necessitate careful thought, monitoring, and research. Paediatric pharmacovigilance aims to address knowledge gaps and improve drug safety for patients. Health care providers play a critical role in ADR detection and reporting. ADRs can vary in intensity and variety among paediatric age groups, making it challenging to identify, report, and manage them. This review briefly elaborates the historical background of paediatric pharmacovigilance and also physiological peculiarities of pharmacodynamics and pharmacokinetic aspects of drugs in newborns, infants, toddlers and children and the importance of paediatric pharmacovigilance system.Mugda Med Coll J. 2025; 8(2): 150-156